(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The case of Indi Gregory is paradigmatic of the ethical and legal issues involved in the decision to withdraw life support from an infant. The purpose of this paper is to analyze the case from a dual perspective, ethical and legal, discussing the issue of best interest of the infants.